Alcamo's fundamentals of microbiology. Body systems edition - Pommerville, Jeffrey C.; Pommerville, Jeffrey C. (Sudbury, MA : Jones and Bartlett Publishers, 2010)
Provides an overview key microbiology concepts relevant to the field of medicine, highlighting the genetics and impact of microorganisms, infectious diseases that affect the various body systems, and environmental and applied microbiology.
Based on: Alcamo's fundamentals of microbiology / Jeffrey C. Pommerville. 8th ed. c2006.
Includes index.
Young Adult
Young Adult
Keywords: Bacterial Infections; Medical microbiology; Medical microbiology; Microbiology; Mycoses; Virus Diseases